Analysis of the proposed law on popular and community-based economy in Colombia - Rosado Rodríguez, Efraín; Mendoza Munar, Lainiver (Cooperativismo & Desarrollo, 2025)
This article analyzes the Popular and Community Economy Bill in Colombia as an initiative to recognize and strengthen an economic sector based on principles of solidarity, self-management, and reciprocity. Drawing on various theoretical perspectives, it examines how this legislative proposal seeks to overcome structural challenges such as informality, precarious employment, and economic exclusion. It also analyzes and identifies the main strengths of the bill, including the legal recognition of grassroots actors, the creation of specialized institutions (the National Council and the Guarantee Fund), and innovative mechanisms for financial inclusion and social protection. However, it also reveals significant risks in its implementation: limitations in participatory processes, the lack of detailed fiscal impact studies, and weaknesses in the design of monitoring mechanisms. Using a methodology that combines legal analysis with public policy evaluation, the article proposes key recommendations to strengthen the initiative: 1) expanding opportunities for citizen participation, 2) ensuring sustainable budgetary resources, and 3) better integrating the new institutions with existing economic policies.
Keywords: Popular economy; Community economy; Inclusion; Economic development; informality